Association of sP-selectin levels and demographic variables with Coronary Artery Disease - Shama Akram, Sana Sarmad, Muhammad Shahroz Humza, Muhammad Adnan Sadiq, Sumera Saghir, Muhammad Fahim ul Haq, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Coronary Artery Diseases (CAD) are among the major causes of global morbidity, mortality and disability. P-selectin, being an adhesion molecule, is found in platelet granules and endothelial cells and plays a vital role in inter-platelet aggregation as well as migration of leukocytes into the vascular wall Objective: The objective of present study was to determine the level of sP Selectin in patients with CAD and compare it with healthy controls in Pakistani population. Moreover, association of CAD with p-selectin levels and other demographic variables were to BE assessed. Correlation of p-selectin levels and gender was also to be assessed. Materials and Methods: It is a cross sectional, analytical study including 60 CAD patients and 60 controls (with ages between 40-60 years, both genders). sP Selectin levels were determined by ELISA. Results: Mean P Selectin serum level in patients was 414.27±216.48 ng/ml with control group mean P Selectin level of 510.88±257.26 ng/ml. Mean P Selectin serum level in males was 438.215 ± 201.54 ng/ml with control group mean P Selectin level of 499.119 ± 290.02 ng/ml. Conclusions: sP Selection levels are higher in control group with a significant difference which can be due to use of antiplatelet drugs. CAD was positively associated with BMI, positive family history, smoking history and history of hypertension. Females had significantly higher p-selectin levels than males. More studies are needed with bigger sample size in our population